Improving quality of care for patients with iron deficiency anemia presenting to the emergency department. Issue 8 (17th April 2018) - Khadadah, Fatima; Callum, Jeannie; Shelton, Dominick; Lin, Yulia
Abstract : BACKGROUND: Patients presenting to the emergency department (ED) with iron deficiency anemia (IDA) are underrecognized, undertreated with iron, and overtransfused. A 3‐month audit of red blood cell (RBC) transfusions at the Sunnybrook Health Sciences Centre ED in 2013 showed that only 53% of transfusions for IDA were appropriate. The aim of this quality improvement project was to increase the rate of appropriate transfusion to greater than 80%. STUDY DESIGN AND METHODS: Since November 2013, several quality improvement interventions have been implemented, including educational presentations, development of an algorithm on IDA management in the ED, and development of an ED IDA toolkit. The primary outcome was appropriateness of RBC transfusions per month. The process measure was monthly intravenous (IV) iron use in IDA patients managed exclusively by ED staff. Balancing measures included IV iron use according to the algorithm and undertransfusion. RESULTS: Over a 24‐month period beginning January 2014, assessment of 193 units transfused in the ED showed an improvement of RBC appropriateness to 91% (range 50%‐100%). IV iron use increased from one dose in the 3‐month audit to an average of 2.6 and 4.7 per month in 2014 and 2015, respectively. IV iron use did not follow the algorithm in 19% (18 of 93) of cases: 12 were given to patients with less severe iron deficiency or bleeding. CONCLUSION: Improved RBC transfusion appropriateness for IDA in the ED can be achieved and maintained with the implementation of simple educational and practical interventions.